Muhammad Arif wins WorldSkills Malaysia Youth represents country in Digital Construction - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 18 November 2022 - Alumnus of Universiti Malaysia Pahang (UMP), Muhammad Arif Irfan A’ali Zaini, who has just completed his Diploma of Civil Engineering, won the WorldSkills Malaysia Youth (WSMB) in Digital Construction organised by the Department of Skills Development, Ministry of Human Resources.